The underworld of art - Naylor, Robin T. (Crime, law and social change, 2008)
Although crime in the market for fine arts has a long historical pedigree, the explosive growth of the market, and the conversion of art (along with collectible goods of all sorts) into speculative assets, that began or at least accelerated in the mid 1970s, focused increasing attention on the phenomenon. At the same time the issue of protecting cultural patrimony became a subject of greater contention between source and market countries, while common law and civil code jurisdictions struggled over how to reconcile approaches to regulation and enforcement. This paper highlights these issues with specific reference to the market for high-end paintings although its lessons are germane to all subdivisions of the collectibles market. It attempts to elucidate the main criminogenic factors - speculative shifts in demand, fraudulent supply, and illegal activity by various intermediary institutions ranging from dealers to appraisers to auction houses, while highlighting the role of collectors, museums, and financial institutions both as victims and active participants. Despite enduring myths about “organized crime,” illegal operations in the art market are the work overwhelmingly of insiders who alone have the technical knowledge and circle of intimates necessary to link an illicit supply with a demand that can range from the strictly legitimate, the legal but dubious, and the explicitly criminal. The critical lesson is that stolen, forged or smuggled material makes its way through much the same circles of intermediaries and ends up for the most part in the same locations and the same hands as artwork of legal origin.